Non-aqueous electrolyte energy storage element

JP2026167269APending Publication Date: 2026-10-14GS YUASA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025060780
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0008】 本発明の一側面によれば、低温条件下での抵抗が低く且つ充放電サイクル後の容量維持率が高い非水電解質蓄電素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167269000001_ABST
    Figure 2026167269000001_ABST
Patent Text Reader

Abstract

The present invention provides a non-aqueous electrolyte energy storage element that exhibits low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles. [Solution] The non-aqueous electrolyte energy storage element comprises a positive electrode having a positive electrode active material layer containing lithium transition metal composite oxide particles and a conductive agent, and a negative electrode having a negative electrode active material layer containing graphite particles, wherein the lithium transition metal composite oxide particles contain nickel, cobalt, and manganese, the nickel content in the lithium transition metal composite oxide particles is 40 mol% or more and the cobalt content is 30 mol% or more of all metal elements other than lithium, the internal porosity of the lithium transition metal composite oxide particles is 15% or more, the conductive agent content in the positive electrode active material layer is 5% by mass or more and 10% by mass or less, the D50 particle size of the graphite particles is 11 μm or more and 16 μm or less, and the ratio of the D10 particle size to the D90 particle size (D10 / D90) of the graphite particles is 0.2 or more and 0.35 or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a non-aqueous electrolyte electricity storage element.

BACKGROUND ART

[0002] Non-aqueous electrolyte secondary batteries, represented by lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles and the like due to their high energy density. As non-aqueous electrolyte electricity storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely prevalent.

[0003] As positive electrode active materials for non-aqueous electrolyte electricity storage elements, LiNi 0.50 Co 0.35 Mn 0.15 Lithium transition metal composite oxides such as O2 have been developed and put into practical use (see Patent Document 1). On the other hand, carbon materials including graphite are widely used for negative electrode active materials.

PRIOR ART DOCUMENTS

PATENT DOCUMENTS

[0004]

PATENT DOCUMENT 1

SUMMARY OF THE INVENTION

PROBLEM TO BE SOLVED BY THE INVENTION

[0005] One of the performances required for non-aqueous electrolyte electricity storage elements is low resistance under low-temperature conditions. However, non-aqueous electrolyte electricity storage elements with low resistance under low-temperature conditions tend to have poor life performance, and it is not easy to achieve both of these properties.

[0006] An object of the present invention is to provide a non-aqueous electrolyte electricity storage element that has low resistance under low-temperature conditions and a high capacity retention rate after charge-discharge cycles.

MEANS FOR SOLVING THE PROBLEM

[0007] A non-aqueous electrolyte energy storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer containing lithium transition metal composite oxide particles and a conductive agent, and a negative electrode having a negative electrode active material layer containing graphite particles, wherein the lithium transition metal composite oxide particles contain nickel, cobalt, and manganese, the content of nickel in the lithium transition metal composite oxide particles is 40 mol% or more and the content of cobalt is 30 mol% or more of all metal elements other than lithium, the internal porosity of the lithium transition metal composite oxide particles is 15% or more, the content of the conductive agent in the positive electrode active material layer is 5% by mass or more and 10% by mass or less, the D50 particle size of the graphite particles is 11 μm or more and 16 μm or less, and the ratio of the D10 particle size to the D90 particle size (D10 / D90) of the graphite particles is 0.2 or more and 0.35 or less. [Effects of the Invention]

[0008] According to one aspect of the present invention, it is possible to provide a non-aqueous electrolyte energy storage element that has low resistance under low temperature conditions and high capacity retention after charge-discharge cycles. [Brief explanation of the drawing]

[0009] [Figure 1] Figure 1 is a perspective view showing a non-aqueous electrolyte energy storage element according to one embodiment of the present invention. [Figure 2] Figure 2 is a schematic diagram showing an energy storage device comprising a non-aqueous electrolyte energy storage element according to multiple embodiments of the present invention. [Modes for carrying out the invention]

[0010] First, an overview of the non-aqueous electrolyte energy storage elements disclosed herein will be provided.

[0011] [1] A non-aqueous electrolyte energy storage element according to one aspect of the present invention comprises a positive electrode having a positive electrode active material layer containing lithium transition metal composite oxide particles and a conductive agent, and a negative electrode having a negative electrode active material layer containing graphite particles, wherein the lithium transition metal composite oxide particles contain nickel, cobalt, and manganese, the content of nickel in the lithium transition metal composite oxide particles is 40 mol% or more and the content of cobalt is 30 mol% or more of all metal elements other than lithium, the internal porosity of the lithium transition metal composite oxide particles is 15% or more, the content of the conductive agent in the positive electrode active material layer is 5% by mass or more and 10% by mass or less, the D50 particle size of the graphite particles is 11 μm or more and 16 μm or less, and the ratio of the D10 particle size to the D90 particle size (D10 / D90) of the graphite particles is 0.2 or more and 0.35 or less.

[0012] The non-aqueous electrolyte energy storage element described in [1] above exhibits low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles. The reason for these effects is not entirely clear, but the following reasons are speculated. Lithium transition metal composite oxides with a high nickel content have a large theoretical capacity per unit mass when used as a positive electrode active material for non-aqueous electrolyte energy storage devices. Therefore, using such lithium transition metal composite oxides as positive electrode active materials enables increased capacity and miniaturization of non-aqueous electrolyte energy storage devices. However, lithium transition metal composite oxides with a high nickel content are prone to cation disorder (specifically, site exchange between lithium ions and nickel ions). It is believed that this cation disorder inhibits the diffusivity of lithium ions in the lithium transition metal composite oxide particles, which is one reason why the resistance of non-aqueous electrolyte energy storage devices using lithium transition metal composite oxides with a high nickel content cannot be sufficiently reduced under low-temperature conditions. One reason for the occurrence of the above-mentioned cation disorder is that the ionic radius of nickel ions existing in the divalent cation state is close to that of lithium ions. Here, in lithium transition metal composite oxides containing nickel, cobalt, and manganese, and with a high nickel content, increasing the cobalt content (i.e., decreasing the manganese content) suppresses the cation disorder. This is thought to be because, in lithium transition metal composite oxides, the cobalt element mainly exists in a trivalent cation state, and the manganese element mainly exists in a tetravalent cation state. Therefore, by reducing the content of manganese, which has a relatively high valency, the nickel element is more likely to exist in a trivalent cation state. By using lithium transition metal composite oxide particles having such a transition metal element composition, and further using those with an internal porosity of 15% or more, the surface area is increased, which can lower the resistance of non-aqueous electrolyte energy storage elements under low-temperature conditions. On the other hand, when lithium transition metal composite oxide particles having the above-described transition metal element composition and a large internal porosity are used, it may be difficult to form uniform conductive paths in the positive electrode active material layer, which can lead to increased degradation of the lithium transition metal composite oxide particles due to current concentration. Furthermore, lithium transition metal composite oxide particles having the above-described transition metal element composition and a large internal porosity are prone to cracking with repeated charging and discharging. Due to the current concentration and cracking of particles due to repeated charging and discharging, transition metal elements tend to dissolve from the lithium transition metal composite oxide particles as ions into the non-aqueous electrolyte. The transition metal elements dissolved into the non-aqueous electrolyte precipitate on the surface of the graphite particles, which are the negative electrode active material. As the graphite particles repeatedly undergo volume changes due to expansion and contraction with charging and discharging, the film formed on the surface of the graphite particles repeatedly collapses and reforms, leading to repeated deposition of transition metal elements and a decrease in discharge capacity. In contrast, by setting the content of the above-described conductive agent in the positive electrode active material layer to 5% by mass or more and 10% by mass or less, it is easier to form uniform conductive paths in the positive electrode active material layer. Furthermore, by setting the D50 particle size of the graphite particles to 11 μm or more and 16 μm or less, and the ratio of the D10 particle size to the D90 particle size (D10 / D90) in the graphite particles to 0.2 or more and 0.35 or less, a particle size distribution in which large and small graphite particles are appropriately mixed is easily formed. In this case, the small-sized graphite particles fill the spaces between the large-sized graphite particles, making it easier for the negative electrode active material layer to have a stable structure with small volume changes due to expansion and contraction during charging and discharging. By homogenizing the conductive paths in the positive electrode active material layer and stabilizing the structure of the negative electrode active material layer as described above, the repeated breakdown and reformation of the film on the surface of the graphite particles and the deposition of transition metal elements are suppressed, and as a result, the decrease in discharge capacity after the charge-discharge cycle of the non-aqueous electrolyte energy storage element is suppressed. For the reasons stated above, it is presumed that the non-aqueous electrolyte energy storage element described in [1] above has low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles.

[0013] The elemental composition ratio of lithium transition metal composite oxide particles is the value of the lithium transition metal composite oxide particles before charging and discharging, or, in the case of lithium transition metal composite oxide particles contained in the positive electrode of a non-aqueous electrolyte energy storage element, the value after processing by the following procedure. First, the non-aqueous electrolyte energy storage element is charged with a constant current of 0.05C until it reaches the charging termination voltage for normal use, and is brought to a fully charged state. After a 30-minute rest, it is discharged with a constant current of 0.05C until it reaches the discharge termination voltage for normal use. It is disassembled, the positive electrode is removed, and a test battery is assembled with the removed positive electrode as the working electrode and a metallic lithium electrode as the counter electrode. Pure metallic lithium is used for the metallic lithium electrode here. For the test battery, with a current of 7mA per gram of positive electrode active material, the positive electrode potential is 2.75V (vs.Li / Li + Constant current discharge is performed until the positive electrode is fully discharged. The device is disassembled again and the positive electrode is removed. The removed positive electrode is washed with dimethyl carbonate. Then, the positive electrode active material layer containing lithium transition metal composite oxide particles is peeled off from the positive electrode substrate, and the positive electrode active material layer is washed with a solvent capable of dissolving the binder to remove the binder. After that, it is washed with water and dried under reduced pressure at room temperature for 24 hours to obtain lithium transition metal composite oxide particles. The obtained lithium transition metal composite oxide particles are subjected to measurement. The work from disassembling the non-aqueous electrolyte energy storage element to obtaining lithium transition metal composite oxide particles is carried out in an argon atmosphere with a dew point of -60°C or lower.

[0014] Here, "under normal use" means using the non-aqueous electrolyte energy storage element under the charge and discharge conditions recommended or specified for that element, and, if equipment for using the non-aqueous electrolyte energy storage element is available, using that equipment.

[0015] "Graphite" refers to the average lattice plane spacing (d) of the (002) plane, determined by X-ray diffraction before charging or in the following complete discharge state. 002 This refers to carbon materials with a nautical radius of 0.33 nm or more and less than 0.34 nm.

[0016] "D50 particle size" refers to the value (D50) at which the volume-based integrated distribution, calculated in accordance with JIS-Z-8819-2 (2001), is 50%, based on the particle size distribution measured by laser diffraction / scattering on a dilution of particles diluted with a solvent, in accordance with JIS-Z-8825 (2013). "D90 particle size" refers to the value (D90) at which the volume-based integrated distribution, calculated as described above, is 90%. "D10 particle size" refers to the value (D10) at which the volume-based integrated distribution, calculated as described above, is 10%. In this specification, the above D50 particle size is also referred to as the "average particle size".

[0017] The X-ray diffraction pattern, average particle size, and BET specific surface area of ​​the graphite particles, as described later, are values ​​for graphite particles before charging and discharging, or, in the case of graphite particles contained in the negative electrode of a non-aqueous electrolyte energy storage element, values ​​obtained after processing according to the following procedure. First, the non-aqueous electrolyte energy storage element is discharged at a constant current of 0.1C to the discharge termination voltage during normal use. It is then disassembled, the negative electrode is removed, and a test battery is assembled using the removed negative electrode as the working electrode and metallic lithium as the counter electrode. Pure metallic lithium is used for the metallic lithium electrode here. For the test battery, with a current of 10mA per gram of negative electrode active material, the closed-circuit potential of the negative electrode is 2.0V (vs.Li / Li + Constant current discharge is performed until the graphite particles are completely discharged. The device is disassembled again, and the negative electrode is removed. The removed negative electrode is washed with dimethyl carbonate. Then, the negative electrode active material layer containing graphite particles is peeled off from the negative electrode substrate, and the negative electrode active material layer is washed with a binder-soluble solvent to remove the binder. The washed negative electrode active material layer is immersed in an acid or alkaline solution to remove metals derived from the negative electrode substrate and the SEI (solid electrolyte interface) coating, etc. Then, it is washed with water and dried under reduced pressure at room temperature for 24 hours to obtain graphite particles. Disassembly of the non-aqueous electrolyte energy storage element and test battery is performed in an argon atmosphere with a dew point of -60°C or lower.

[0018] X-ray diffraction measurements of carbon materials (graphite particles) are performed using powder X-ray diffraction with an X-ray diffractometer (Rigaku "MiniFlex II"), with a CuKα source, a tube voltage of 30kV, and a tube current of 15mA. The diffracted X-rays pass through a 30μm thick Kβ filter and are detected by a high-speed one-dimensional detector (D / teX Ultra 2). The sampling width is 0.02°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13mm (OPEN), and the scattering slit width is 8mm. The Kα2 line is removed from the CuKα line, and an X-ray diffraction pattern based on the Kα1 line is obtained.

[0019] The "internal porosity" of lithium transition metal composite oxide particles and the "internal porosity" of graphite particles, as described later, refer to the ratio of the area of ​​voids within the particle to the total area of ​​the particle, as observed in the cross-section of the particle in the SEM image obtained using a scanning electron microscope (SEM). The "internal porosity (ratio of the area of ​​voids within the particle to the total area of ​​the particle)" of lithium transition metal composite oxide particles and graphite particles is determined by the following procedure. (1) Preparation of the sample for measurement The positive and negative electrodes to be measured are fixed with thermosetting resin. The cross-sections of the resin-fixed positive and negative electrodes are exposed by ion milling to prepare samples for measurement. The positive and negative electrodes to be measured shall be prepared according to the following procedure. If the positive and negative electrodes of the non-aqueous electrolyte energy storage element can be prepared before assembly, they shall be used as is. If the electrodes are to be prepared from an assembled non-aqueous electrolyte energy storage element, first discharge the non-aqueous electrolyte energy storage element at a constant current of 0.1C until it reaches the discharge termination voltage during normal use. Disassemble the element, remove the positive and negative electrodes, thoroughly wash them with dimethyl carbonate, and then dry them under reduced pressure at room temperature for 24 hours. All work from disassembling the non-aqueous electrolyte energy storage element to preparing the positive and negative electrodes to be measured shall be carried out in a dry air atmosphere with a dew point of -40°C or lower. (2) Acquisition of SEM images For acquiring SEM images, a JSM-7001F (manufactured by JEOL Ltd.) will be used as the SEM. The SEM image will be a secondary electron image. The acceleration voltage will be 5kV. The observation magnification will be set so that 3 to 15 lithium transition metal composite oxide particles or graphite particles appear in one field of view. The obtained SEM image will be saved as an image file. Other conditions such as spot diameter, working distance, irradiation current, brightness, and focus will be set appropriately so that the outlines of the lithium transition metal composite oxide particles or graphite particles are clear. (3) Cutting out the outline of lithium transition metal composite oxide particles or graphite particles Using the image cropping function of Adobe Photoshop Elements 11, the outlines of lithium transition metal composite oxide particles or graphite particles are cropped from the acquired SEM image. This outline cropping is done by selecting the area outside the outline of the lithium transition metal composite oxide particles or graphite particles using the Quick Selection Tool, and editing everything except the lithium transition metal composite oxide particles or graphite particles into a black background. If fewer than three lithium transition metal composite oxide particles or graphite particles have had their outlines cropped, the SEM image is acquired again and this process is repeated until three or more lithium transition metal composite oxide particles or graphite particles have had their outlines cropped. (4) Binarization process For the image of the first lithium transition metal composite oxide particle or graphite particle from the cropped image, the image analysis software PopImaging 6.00 is used to perform binarization, setting the threshold to a concentration 20% lower than the concentration that yields the maximum intensity. By performing binarization, the area of ​​the higher concentration side is calculated and defined as the "area of ​​voids within the particle S1". Next, the same first image of lithium transition metal composite oxide particles or graphite particles as before is subjected to binarization with a density threshold of 10%. Through binarization, the outer edge of the lithium transition metal composite oxide particles or graphite particles is determined, and the area inside that outer edge is calculated to be the "total particle area S0". Using the S1 and S0 calculated above, the ratio of S1 to S0 (S1 / S0) is calculated to determine the "area ratio R1 of voids within the particle relative to the total area of ​​the particle" in the first lithium transition metal composite oxide particle or graphite particle. For the images of the second and subsequent lithium transition metal composite oxide particles or graphite particles from the cropped images, the same binarization process described above is performed on each to calculate the areas S1 and S0. Based on these calculated areas S1 and S0, the area ratios R2, R3, ... of the voids in each lithium transition metal composite oxide particle or graphite particle are calculated. (5) Determination of the area ratio of voids In lithium transition metal composite oxide particles or graphite particles, the "internal porosity (the ratio of the area of ​​voids within a particle to the total area of ​​the particle)" is determined by calculating the average value of the area ratios R1, R2, R3, ... of all voids calculated by binarization. In addition, instead of the scanning electron microscope used for "acquisition of SEM images," the image editing software used for "outline extraction of lithium transition metal composite oxide particles or graphite particles," and the image analysis software used for "binarization processing," equivalent devices and software capable of measurement, image editing, and image analysis may be used.

[0020] [2] In the non-aqueous electrolyte energy storage element described in [1] above, the internal porosity of the graphite particles may be 2% or less.

[0021] In the non-aqueous electrolyte energy storage element described in [2] above, graphite particles with a small internal porosity experience less volume change due to expansion and contraction during charging and discharging. This suppresses the repeated breakdown and reformation of the coating formed on the surface of the graphite particles, as well as the deposition of transition metal elements. As a result, the decrease in discharge capacity after charge-discharge cycles is further suppressed.

[0022] [3] In the non-aqueous electrolyte energy storage element described in [1] or [2] above, the BET specific surface area of ​​the graphite particles is 3m 2 It may be less than / g.

[0023] The non-aqueous electrolyte energy storage element described in [3] above can achieve a higher capacity retention rate after charge-discharge cycles, among other things.

[0024] The "BET specific surface area" of graphite particles shall be the value obtained by the following procedure: 1.00 g of graphite particles is placed in a sample tube for measurement and dried under reduced pressure at 120°C for 12 hours. Next, adsorption isotherms are measured using the nitrogen gas adsorption method with liquid nitrogen, within the range of relative pressure P / P0 (P0 = approximately 770 mmHg) from 0 to 1. The measuring device used is the "autosorb iQ" manufactured by Quantachrome. Five points are extracted from the region of P / P0 = 0.05 to 0.3 of the obtained adsorption isotherms, and a BET plot is performed. The BET specific surface area is calculated from the y-intercept and slope of the resulting line.

[0025] [4] In the non-aqueous electrolyte energy storage element described in any one of [1] to [3] above, the molar ratio of the content of the cobalt element to the content of the manganese element in the lithium transition metal composite oxide particles may be 1.2 or more.

[0026] The non-aqueous electrolyte energy storage element described in [4] above can achieve lower resistance under low-temperature conditions. The following reasons are presumed to be the cause of this: As mentioned above, the cobalt element in the lithium transition metal composite oxide mainly exists in a trivalent cation state, the manganese element mainly exists in a tetravalent cation state, and the presence of nickel element in a divalent cation state is a factor that causes cation disorder. Therefore, by increasing the molar ratio of the cobalt element, which mainly exists in a trivalent cation state, to the manganese element, which mainly exists in a tetravalent cation state, the nickel element is more likely to exist in a trivalent cation state than in a divalent cation state. As a result, the amount of nickel element in a divalent cation state is reduced, making cation disorder less likely to occur, and thus the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions is presumed to be lower.

[0027] A non-aqueous electrolyte energy storage element, a method for manufacturing a non-aqueous electrolyte energy storage element, an energy storage device, and other embodiments according to one embodiment of the present invention will be described in detail below.

[0028] <Non-aqueous electrolyte energy storage element> A non-aqueous electrolyte energy storage element according to one embodiment of the present invention comprises a positive electrode, a negative electrode, a non-aqueous electrolyte, and a container housing them. The non-aqueous electrolyte energy storage element may further include a separator interposed between the positive electrode and the negative electrode to electrically insulate them. The positive electrode, the negative electrode, and any separator typically constitute an electrode body. At least a portion of the non-aqueous electrolyte is typically present in a state of permeation into the electrode body. The non-aqueous electrolyte energy storage element according to one embodiment of the present invention may further include other components. The non-aqueous electrolyte energy storage element according to one embodiment of the present invention, by having the configuration detailed below, exhibits low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles.

[0029] For example, the non-aqueous electrolyte energy storage element 1 shown in Figure 1, according to one embodiment of the present invention, comprises an electrode body 2, a non-aqueous electrolyte (not shown), and a rectangular parallelepiped container 3 that houses them. The non-aqueous electrolyte energy storage element 1 in Figure 1 further comprises a positive electrode lead 4, a positive electrode external terminal 5, a negative electrode lead 6, and a negative electrode external terminal 7. The positive electrode lead 4 and the negative electrode lead 6 are housed together with the electrode body 2, etc., inside the container 3. The positive electrode external terminal 5 and the negative electrode external terminal 7 are provided outside the container 3. The positive electrode constituting the electrode body 2 is electrically connected to the positive electrode external terminal 5 via the positive electrode lead 4. The negative electrode constituting the electrode body 2 is electrically connected to the negative electrode external terminal 7 via the negative electrode lead 6.

[0030] The non-aqueous electrolyte energy storage element of the present invention may also be a non-aqueous electrolyte secondary battery. Below, the main components constituting the non-aqueous electrolyte energy storage element according to one embodiment of the present invention will be described in detail, focusing on the case where the non-aqueous electrolyte energy storage element is a non-aqueous electrolyte secondary battery (particularly a lithium-ion secondary battery), but this is not intended to limit the scope of application of the present invention.

[0031] Note that any combination of the lower limit value and the upper limit value of each numerical range described in the embodiments of the present invention is permissible.

[0032] (Positive Electrode) The positive electrode has a positive electrode substrate, and a positive electrode active material layer laminated on the positive electrode substrate directly or via an intermediate layer. Usually, the positive electrode has a portion where the positive electrode substrate is exposed. This exposed portion of the positive electrode substrate is normally connected to the aforementioned positive electrode lead. The positive electrode may have a shape such as, for example, a sheet shape, a plate shape, or a strip shape.

[0033] The thickness of the positive electrode is appropriately set according to the application and the like of the non-aqueous electrolyte power storage element. The average thickness of the positive electrode may be, for example, 30 μm or more and 1,000 μm or less. The lower limit of the average thickness of the positive electrode may be 50 μm, 100 μm, or 200 μm. The upper limit of the average thickness of the positive electrode may be 500 μm, 400 μm, 300 μm, 200 μm, or 100 μm. The average thickness of the positive electrode refers to the average thickness of the portion where the positive electrode active material layer is laminated on the positive electrode substrate directly or via an intermediate layer. When both a portion where the positive electrode active material layer is laminated on both surfaces of the positive electrode substrate and a portion where the positive electrode active material layer is laminated on only one surface of the positive electrode substrate exist, the average thickness refers to the average thickness of the portion where the positive electrode active material layer is laminated on both surfaces of the positive electrode substrate. In addition, as used in the present specification, "average thickness" means the average value of thicknesses measured at any 5 positions.

[0034] The positive electrode substrate has electrical conductivity. As used in the present specification, "has electrical conductivity" means that the volume resistivity is 10 -2 Ω·cm or less. The volume resistivity is a value measured in accordance with JIS-H-0505 (1975). On the other hand, as used in the present specification, "does not have electrical conductivity" or "has (electrical) insulating properties" means that the aforementioned volume resistivity is 10 7 Ω·cm or more.

[0035] Examples of materials for the positive electrode substrate include metals such as aluminum, titanium, iron, and their alloys (stainless steel, etc.). Among these, aluminum or aluminum alloys are preferred from the viewpoint of high potential resistance, high electronic conductivity, and cost.

[0036] The positive electrode substrate has a shape such as a sheet, plate, or strip. Examples of positive electrode substrate forms include foil, vapor-deposited film, mesh, and porous material, with foil being preferred. The positive electrode substrate may also be, for example, aluminum foil or aluminum alloy foil.

[0037] The average thickness of the positive electrode substrate may be, for example, 3 μm or more and 50 μm or less. The lower limit of the average thickness of the positive electrode substrate may be 5 μm, 8 μm, 10 μm, or 15 μm. The upper limit of the average thickness of the positive electrode substrate may be 40 μm, 30 μm, 20 μm, or 15 μm.

[0038] The intermediate layer is a layer placed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer includes, for example, a conductive agent and a binder. When the intermediate layer contains a conductive agent, the contact resistance between the positive electrode substrate and the positive electrode active material layer can be reduced. Examples of conductive agents and binders used in the intermediate layer are the same as those used in the positive electrode active material layer, which will be described later.

[0039] The positive electrode active material layer contains lithium transition metal composite oxide particles as the positive electrode active material and a conductive agent. The positive electrode active material layer may optionally contain components such as a binder, thickener, and filler. The positive electrode active material layer may be formed from a positive electrode mixture containing the positive electrode active material, conductive agent, and other optional components. The positive electrode active material layer may be provided on only one side of a positive electrode substrate having a shape such as a sheet, or on both sides.

[0040] The lithium transition metal composite oxide particles contain nickel, cobalt, and manganese. These lithium transition metal composite oxide particles typically have an α-NaFeO2 type crystal structure.

[0041] The lower limit of the nickel content in lithium transition metal composite oxide particles, relative to all metal elements other than lithium, is 40 mol%, preferably 42 mol%, and more preferably 44 mol%. A nickel content above this lower limit allows for increased capacity, miniaturization, and weight reduction of the non-aqueous electrolyte energy storage element. On the other hand, the upper limit of the nickel content is preferably 60 mol%, more preferably 55 mol%, even more preferably 50 mol%, and even more preferably 48 mol%. A nickel content below this upper limit allows for increased thermal stability of the non-aqueous electrolyte energy storage element and improved capacity retention after charge-discharge cycles.

[0042] The lower limit of the cobalt content in lithium transition metal composite oxide particles, relative to all metal elements other than lithium, is 30 mol%, preferably 32 mol%, and more preferably 34 mol%. A cobalt content above this lower limit allows for lower resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions. On the other hand, the upper limit of the cobalt content is preferably 50 mol%, more preferably 45 mol%, even more preferably 40 mol%, and even more preferably 38 mol%.

[0043] The lower limit of the manganese content in lithium transition metal composite oxide particles, relative to all metal elements other than lithium, is preferably 5 mol%, more preferably 10 mol%, and still more preferably 15 mol%. On the other hand, the upper limit of the manganese content is preferably 30 mol%, more preferably 28 mol%, still more preferably 25 mol%, and still more preferably 23 mol%.

[0044] The lower limit of the molar ratio (Co / Mn) of cobalt element content to manganese element content in lithium transition metal composite oxide particles is preferably 1.2, more preferably 1.5, even more preferably 1.6, and even more preferably 1.7. A molar ratio (Co / Mn) above this lower limit allows for lower resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions. The upper limit of the molar ratio (Co / Mn) may be, for example, 3.0, or 2.5, 2.0, 1.9, or 1.8.

[0045] The lithium transition metal composite oxide particles may further contain other transition metal elements other than nickel, cobalt, and manganese, as well as typical metal elements other than lithium, such as aluminum. However, the lower limit of the total content of nickel, cobalt, and manganese in all metal elements other than lithium in the lithium transition metal composite oxide particles is preferably 90 mol%, more preferably 95 mol%, and even more preferably 99 mol%. The metal elements other than lithium in the lithium transition metal composite oxide particles may be substantially composed of only three elements: nickel, cobalt, and manganese. When the metal elements other than lithium in the lithium transition metal composite oxide particles are substantially composed of only three elements: nickel, cobalt, and manganese, the effects of low resistance under low temperature conditions and high capacity retention after charge-discharge cycles of the non-aqueous electrolyte energy storage element are particularly well achieved.

[0046] The lower limit of the molar ratio of lithium to all other metal elements in lithium transition metal composite oxide particles may be 1.0. The upper limit of the molar ratio of lithium to all other metal elements in lithium transition metal composite oxide particles may be 1.5, 1.4, 1.3, 1.2, 1.1, 1.05, or 1.0.

[0047] Lithium transition metal composite oxide particles may be formed from a compound represented by the following formula (1). Li1+α Me 1-α O2···(1) In equation (1), Me is a metallic element other than Li, including Ni, Co, and Mn. However, the Ni content in Me is 40 mol% or more, and the Co content in Me is 30 mol% or more. 0 ≤ α < 1.

[0048] The preferred content of each element in the compound represented by formula (1) above is the same as the preferred content of each element described in the explanation of lithium transition metal composite oxide particles above.

[0049] Lithium transition metal composite oxide particles are particles that have voids inside. Lithium transition metal composite oxide particles are typically secondary particles formed by the aggregation of multiple primary particles. The lower limit of the internal porosity of lithium transition metal composite oxide particles is 15%, preferably 16%, more preferably 17%, and even more preferably 18%. Having an internal porosity of lithium transition metal composite oxide particles above the above lower limit can lower the resistance of non-aqueous electrolyte energy storage elements under low-temperature conditions. The upper limit of the internal porosity of lithium transition metal composite oxide particles is preferably 30%, more preferably 25%, and even more preferably 22%. Having an internal porosity of lithium transition metal composite oxide particles below the above upper limit can further improve the capacity retention rate of non-aqueous electrolyte energy storage elements after charge-discharge cycles. Lithium transition metal composite oxide particles with an internal porosity of 15% or more can be manufactured by known methods.

[0050] The average particle size of the lithium transition metal composite oxide particles is preferably, for example, 0.1 μm to 20 μm, more preferably 0.5 μm to 10 μm, even more preferably 1 μm to 8 μm, even more preferably 2 μm to 6 μm, and may also be 3 μm to 5 μm. Setting the average particle size of the lithium transition metal composite oxide particles to or above the lower limit makes it easier to manufacture or handle the lithium transition metal composite oxide particles. Setting the average particle size of the lithium transition metal composite oxide particles to or below the upper limit improves the electronic conductivity of the positive electrode active material layer. Known methods using, for example, a pulverizer or classifier can be used to obtain particles such as lithium transition metal composite oxide particles with a predetermined particle size.

[0051] The content of lithium transition metal composite oxide particles in the positive electrode active material layer is preferably 70% to 99% by mass, more preferably 80% to 98% by mass, and may also be 90% to 95% by mass. By setting the content of lithium transition metal composite oxide particles within the above range, it is possible to achieve both high energy density and manufacturability in the positive electrode active material layer, as well as lower the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions.

[0052] The positive electrode active material layer may contain other positive electrode active materials besides the lithium transition metal composite oxide particles described above. Various conventionally known positive electrode active materials can be used as the other positive electrode active material. However, the content of the lithium transition metal composite oxide particles in the total positive electrode active material is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be substantially 100% by mass. By mainly using the lithium transition metal composite oxide particles as the positive electrode active material, the effects of low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles in the non-aqueous electrolyte energy storage element are particularly well achieved.

[0053] The total content of the positive electrode active material in the positive electrode active material layer is preferably 70% to 99% by mass, more preferably 80% to 98% by mass, and may also be 90% to 95% by mass. By setting the total content of the positive electrode active material within the above range, it is possible to achieve both high energy density and manufacturability in the positive electrode active material layer, as well as lower the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions.

[0054] Conductive agents are typically components made of conductive materials. Even if the volume resistivity of a conductive agent cannot be directly measured, if the volume resistivity is 10 -2 Materials whose conductivity is known to be Ω·cm or less are classified as conductive agents. Examples of conductive agents include carbon materials, metals, and conductive ceramics. A carbon material is a material whose main constituent element is carbon. The main constituent element is the element that is present in the largest quantity by mass. For example, the carbon content in a carbon material may be 80% by mass or more, 90% by mass or more, 95% by mass, 99% by mass, or 99.9% by mass or more. It is preferable that the carbon material is a carbon material other than a non-carbonized polymer compound. Examples of carbon materials include graphite, non-graphitic carbon, and graphene-based carbon. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, and carbon black. Examples of carbon black include furnace black, acetylene black, and Ketjen black. Examples of graphene-based carbon include graphene, carbon nanotubes (CNTs), and fullerenes. Conductive agents can take the form of powder or fibers. One or more conductive agents can be used. These materials may be used in combination as conductive agents. For example, a material made by combining carbon black and CNTs may be used.

[0055] The lower limit of the conductive agent content in the positive electrode active material layer is 5% by mass, preferably 5.5% by mass, and more preferably 6.0% by mass. A conductive agent content above this lower limit can further improve the capacity retention rate after charge-discharge cycles of the non-aqueous electrolyte energy storage element. The upper limit of the conductive agent content in the positive electrode active material layer is 10% by mass, preferably 9% by mass, more preferably 8% by mass, and even more preferably 7.5% by mass. A conductive agent content below this upper limit can increase the energy density of the non-aqueous electrolyte energy storage element.

[0056] Examples of binders include water-based binders and organic solvent-based binders.

[0057] A water-based binder is a binder that dissolves or disperses in water. A water-based binder may be one that dissolves or disperses in 100 parts by mass or more per 100 parts by mass of water at 20°C. When forming a positive electrode active material layer using a positive electrode mixture paste in which the dispersion medium is water or a mixed solvent mainly composed of water, a water-based binder (water-soluble or water-dispersible polymer material) can be used. Examples of water-based binders include polyethylene oxide, polypropylene oxide, polyvinyl alcohol, polyacrylic acid, polymethacrylic acid, polytetrafluoroethylene, styrene-butadiene rubber, polyethylene, polypropylene, nitrile-butadiene rubber, and cellulose.

[0058] An organic solvent-based binder is a binder that dissolves or disperses in an organic solvent (e.g., N-methylpyrrolidone). An organic solvent-based binder may be a binder that dissolves or disperses at 1 part by mass or more per 100 parts by mass of an organic solvent (e.g., N-methylpyrrolidone) at 20°C. When forming a positive electrode active material layer using a positive electrode mixture paste in which the dispersion medium is an organic solvent or a mixed solvent mainly composed of an organic solvent, an organic solvent-based binder (a polymer material having solubility or dispersibility in an organic solvent) can be used. Examples of organic solvent-based binders include polyvinylidene fluoride, copolymers of vinylidene fluoride and hexafluoropropylene, copolymers of ethylene and vinyl alcohol, polyacrylonitrile, polyphosphazene, polysiloxane, polyvinyl acetate, polymethyl methacrylate, polystyrene, polycarbonate, polyamide, polyimide, polyamideimide, crosslinked polymers of cellulose and chitosan pyrrolidone carboxylate, and derivatives of chitosan.

[0059] The binder may be a fluororesin (polytetrafluoroethylene, polyvinylidene fluoride, etc.), a polyolefin (polyethylene, polypropylene, etc.), an elastomer (ethylene propylene diene rubber, styrene butadiene rubber, fluororubber, etc.), a polysaccharide polymer (cellulose, chitosan derivatives, etc.), etc. One or more types of binders may be used.

[0060] The binder content in the positive electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, more preferably 0.5% by mass or more and 9% by mass or less, and even more preferably 1% by mass or more and 8% by mass or less. The upper limit of the binder content may be 5% by mass, 4% by mass, or 3% by mass. By setting the binder content within the above range, the positive electrode active material can be stably maintained. The technology disclosed herein can also be implemented in a form in which the positive electrode active material layer does not contain a binder.

[0061] Examples of thickening agents include polysaccharide polymers such as carboxymethylcellulose and methylcellulose. If the thickening agent has a functional group that reacts with lithium, etc., this functional group may be deactivated beforehand by methylation or the like. The thickening agent may also function as a binder. One or more types of thickening agents can be used. When the positive electrode active material layer contains a thickening agent, the content of the thickening agent in the positive electrode active material layer is preferably 0.1% by mass or more and 8% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less. The technology disclosed herein can also be carried out in a form in which the positive electrode active material layer does not contain a thickening agent.

[0062] The filler is not particularly limited. The filler may be a component other than the positive electrode active material, conductive agent, binder, and thickener, and may be a component that is intentionally included. The filler may be included as a component that fills gaps in the positive electrode active material layer, or it may be included for other purposes. The filler may be an organic substance such as a polyolefin, or an inorganic substance such as an inorganic oxide, hydroxide, or carbonate. One or more types of fillers may be used. When the positive electrode active material layer contains a filler, the filler content in the positive electrode active material layer can be 0.1% by mass or more and 8% by mass or less, usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can also be carried out in a form in which the positive electrode active material layer does not contain a filler.

[0063] The positive electrode active material layer may further contain other components besides the positive electrode active material, conductive agent, binder, thickener, and filler. These other components may include those unintentionally present in the positive electrode active material layer. Furthermore, the positive electrode active material layer may contain impurities unintentionally present as these other components, insofar as they achieve the effects of the present invention. The upper limit of the content of these other components in the positive electrode active material layer may be 10% by mass, 5%, 2%, 1%, 0.1%, or 0.01% by mass. The upper limit of the content of unintentionally present components in the positive electrode active material layer may be 10% by mass, 5%, 2%, 1%, 0.1%, or 0.01% by mass. The upper limit of the content of unintentionally present impurities in the positive electrode active material layer may be 10% by mass, 5%, 2%, 1%, 0.1%, or 0.01% by mass.

[0064] The thickness of the positive electrode active material layer is set appropriately according to the type of positive electrode active material, the application of the non-aqueous electrolyte energy storage element, etc. The average thickness of one positive electrode active material layer may be, for example, 5 μm or more and 1,000 μm or less. The lower limit of the average thickness of one positive electrode active material layer may be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, or 100 μm. The upper limit of the average thickness of one positive electrode active material layer may be 800 μm, 500 μm, 200 μm, 100 μm, 80 μm, 60 μm, or 40 μm. The mass per unit area of ​​one positive electrode active material layer may be, for example, 3 mg / cm². 2 More than 100mg / cm 2 The following is also acceptable: The lower limit of the mass per unit area of ​​one positive electrode active material layer is 5 mg / cm². 2 , 7 mg / cm³ 2 or 10 mg / cm³ 2 It may also be the case that the upper limit of the mass per unit area of ​​one positive electrode active material layer is 50 mg / cm². 2 , 20 mg / cm³ 2 , 15 mg / cm³ 2 , 12 mg / cm³ 2 or 10 mg / cm³ 2 That's fine.

[0065] The porosity of the positive electrode active material layer may be, for example, 20% or more and 50% or less. The lower limit of the porosity of the positive electrode active material layer may be 25%, 30%, or 35%. The upper limit of the porosity of the positive electrode active material layer may be 45%, 40%, or 35%. The "porosity (%)" of the positive electrode active material layer and the negative electrode active material layer described later is calculated using the formula (1-V2 / V1)×100, where V1 is the apparent volume (volume including voids) of the positive (negative) electrode active material layer and V2 is the sum of the actual volumes of each material constituting the positive (negative) electrode active material layer. The sum of the actual volumes V2 of each material constituting the positive (negative) electrode active material layer can be calculated from the content of each material in the positive (negative) electrode active material layer and the true density of each material.

[0066] (Method of manufacturing the positive electrode) The positive electrode can be manufactured by known methods. For example, the positive electrode can be manufactured by applying a paste-like positive electrode mixture (positive electrode mixture paste) directly to a positive electrode substrate or via an intermediate layer, and then drying it to form a positive electrode active material layer. The positive electrode mixture paste typically contains lithium transition metal composite oxide particles, a conductive agent, other optional components, and a dispersion medium. After drying, the positive electrode active material layer may be subjected to pressing or other processes.

[0067] (Negative electrode) The negative electrode comprises a negative electrode substrate and a negative electrode active material layer laminated directly to the negative electrode substrate or via an intermediate layer. Typically, the negative electrode has a portion where the negative electrode substrate is exposed. This exposed portion of the negative electrode substrate is usually connected to the negative electrode lead described above. The negative electrode may have a shape such as a sheet, plate, or strip.

[0068] The thickness of the negative electrode is set appropriately according to the application of the non-aqueous electrolyte energy storage element. The average thickness of the negative electrode may be, for example, 30 μm or more and 1,000 μm or less. The lower limit of the average thickness of the negative electrode may be 50 μm, 100 μm, or 200 μm. The upper limit of the average thickness of the negative electrode may be 500 μm, 400 μm, 300 μm, 200 μm, or 100 μm. The average thickness of the negative electrode is the average thickness of the portion in which the negative electrode active material layer is laminated directly to the negative electrode substrate or via an intermediate layer. If there are portions in which the negative electrode active material layer is laminated on both sides of the negative electrode substrate and portions in which the negative electrode active material layer is laminated on only one side of the negative electrode substrate, then the average thickness of the portion in which the negative electrode active material layer is laminated on both sides of the negative electrode substrate shall be used.

[0069] The negative electrode substrate is electrically conductive. Examples of materials for the negative electrode substrate include metals such as copper, nickel, iron, and their alloys (such as stainless steel), as well as carbon materials. Among these, copper or copper alloys are preferred.

[0070] The negative electrode substrate has a shape such as a sheet, plate, or strip. Examples of negative electrode substrate forms include foil, vapor-deposited film, mesh, and porous material, with foil being preferred. The negative electrode substrate may also be, for example, copper foil or copper alloy foil.

[0071] The average thickness of the negative electrode substrate may be, for example, 2 μm or more and 35 μm or less. The lower limit of the average thickness of the negative electrode substrate may be 3 μm, 4 μm, 5 μm, or 10 μm. The upper limit of the average thickness of the negative electrode substrate may be 30 μm, 20 μm, 15 μm, or 10 μm.

[0072] The configuration of the negative electrode intermediate layer is not particularly limited; for example, it can be selected from the configurations exemplified for the positive electrode intermediate layer.

[0073] The negative electrode active material layer contains graphite particles as the negative electrode active material. The negative electrode active material layer optionally contains optional components such as conductive agents, binders, thickeners, and fillers. The optional components such as conductive agents, binders, thickeners, and fillers can be selected from the materials exemplified above for the positive electrode. The negative electrode active material layer may be formed from a negative electrode mixture containing the negative electrode active material and other optional components. The negative electrode active material layer may be provided on only one side of a negative electrode substrate having a shape such as a sheet, or it may be provided on both sides.

[0074] Graphite particles are components that function as the negative electrode active material. The upper limit of the internal porosity of the graphite particles contained in the negative electrode active material layer is preferably 2%, more preferably 1%, and even more preferably 0.7%. By keeping the internal porosity of the graphite particles below the above upper limit, volume changes due to expansion and contraction of the graphite particles during charging and discharging are suppressed, and the capacity retention rate after the charge-discharge cycle of the non-aqueous electrolyte energy storage element can be improved. The lower limit of the internal porosity of the graphite particles may be 0%, 0.1%, 0.2%, or 0.3%. Graphite particles with an internal porosity of 2% or less can be obtained by compressing conventional general graphite.

[0075] The graphite particles may be natural graphite or synthetic graphite, but natural graphite is preferred. Using natural graphite particles allows for lower resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions, among other things.

[0076] Natural graphite is a general term for graphite obtained from natural resources. Graphite particles made from natural graphite may also be spheroidized natural graphite particles obtained by spheroidizing flake-like natural graphite. Natural graphite may exhibit four peaks in the X-ray diffraction pattern using CuKα rays, measured before charging / discharging or during the discharge state, in the diffraction angle 2θ range of 40° to 50°. These four peaks are considered to consist of two peaks originating from a hexagonal crystal system and two peaks originating from a rhombohedral crystal system. In the case of artificial graphite, generally, only two peaks originating from a hexagonal crystal system are considered to appear. In the X-ray diffraction pattern, the ratio of the peak intensity originating from the (012) plane to the peak intensity originating from the (100) plane ((012) / (100)) is preferably 0.3 or higher, and more preferably 0.4 or higher. The above peak intensity ratio ((012) / (100)) is preferably 0.6 or lower. Here, the (100) plane originates from the hexagonal crystal system structure, and the (012) plane originates from the rhombohedral crystal system structure.

[0077] For example, the upper limit of the BET specific surface area of ​​graphite particles is 5 m². 2 / g or 4m 2 / g is also acceptable, but 3m 2 It is preferable that it be / g, and 2.9m 2 It is more preferable that the BET specific surface area of ​​the graphite particles is below the above upper limit, which allows for a higher capacity retention rate after charge-discharge cycles of the non-aqueous electrolyte energy storage element. The lower limit of the BET specific surface area of ​​the graphite particles is 1 m 2 / g is preferred, 2m 2 / g is more preferable, 2.5m 2 / g is even more preferable. By having a BET specific surface area of ​​graphite particles above the above lower limit, it is possible to further reduce the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions.

[0078] The upper limit for the D50 particle size of the graphite particles is 16 μm, preferably 15 μm, and more preferably 14 μm. By having a D50 particle size of graphite particles below the above upper limit, the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions can be further reduced. The lower limit for the D50 particle size of graphite particles is 11 μm, preferably 11.5 μm. By having a D50 particle size of graphite particles above the above lower limit, the capacity retention rate after charge-discharge cycles of the non-aqueous electrolyte energy storage element can be further increased.

[0079] The upper limit of the ratio of D10 particle size to D90 particle size (D10 / D90) of graphite particles is 0.35, preferably 0.33, and more preferably 0.31. The lower limit of D10 / D90 is 0.2, preferably 0.22, and more preferably 0.24. By keeping D10 / D90 within the above range, it is possible to further increase the capacity retention rate after charge-discharge cycles of the non-aqueous electrolyte energy storage element. Methods for achieving D10 / D90 within the above range include classifying the graphite particles and mixing two or more types of graphite particles with different D50 particle size or particle size distribution.

[0080] The graphite particle content in the negative electrode active material layer is preferably 60% by mass or more and 99.5% by mass or less. The lower limit of the graphite particle content in the negative electrode active material layer is more preferably 80% by mass, 90% by mass, 95% by mass, 97% by mass, or 98% by mass. By setting the graphite particle content within the above range, it is possible to achieve both high energy density and manufacturability in the negative electrode active material layer, as well as lower the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions and improve the capacity retention rate after charge-discharge cycles.

[0081] The negative electrode active material layer may contain other negative electrode active materials besides graphite particles. Various conventionally known negative electrode active materials can be used as the other negative electrode active materials. However, the content of graphite particles in the total negative electrode active materials contained in the negative electrode active material layer is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 99% by mass or more, and may be substantially 100% by mass. By mainly using graphite particles as the negative electrode active material, the effects of low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles of the non-aqueous electrolyte energy storage element are particularly well achieved.

[0082] The total content of all negative electrode active materials in the negative electrode active material layer is preferably 60% by mass or more and 99.5% by mass or less. The lower limit of the total content of all negative electrode active materials in the negative electrode active material layer is more preferably 80% by mass, 90% by mass, 95% by mass, 97% by mass, or 98% by mass. By setting the total content of all negative electrode active materials within the above range, it is possible to achieve both high energy density and manufacturability in the negative electrode active material layer, as well as lower the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions and improve the capacity retention rate after charge-discharge cycles.

[0083] If the negative electrode active material layer contains a conductive agent, the content of the conductive agent in the negative electrode active material layer may be, for example, 1% by mass or more and 10% by mass or less. Preferably, the content of the conductive agent in the negative electrode active material layer is 5% by mass or less, and more preferably 2% by mass or less, 1% by mass or less, 0.1% by mass or less, or 0% by mass. If the content of the conductive agent in the negative electrode active material layer is low or does not contain a conductive agent, the content of the negative electrode active material such as graphite particles can be increased, thereby increasing the energy density of the negative electrode active material layer. Note that graphite particles in the negative electrode active material layer do not count as a conductive agent in the negative electrode active material layer.

[0084] When the negative electrode active material layer contains a binder, the binder content in the negative electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 0.5% by mass or more and 8% by mass or less. The binder content in the negative electrode active material layer may be 5% by mass or less, 2% by mass or less, or 1% by mass or less. The technology disclosed herein can also be carried out in a form in which the negative electrode active material layer does not contain a binder.

[0085] When the negative electrode active material layer contains a thickening agent, the content of the thickening agent in the negative electrode active material layer is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 0.3% by mass or more and 8% by mass or less. The content of the thickening agent in the negative electrode active material layer may be 5% by mass or less, 2% by mass or less, or 1% by mass or less. The technology disclosed herein can also be carried out in a form in which the negative electrode active material layer does not contain a thickening agent.

[0086] The filler in the negative electrode active material layer is a component other than the negative electrode active material, conductive agent, binder, and thickener, and may be a component that is intentionally included. The filler may be included as a component that fills gaps in the negative electrode active material layer, or it may be included for other purposes. When the negative electrode active material layer contains a filler, the filler content in the negative electrode active material layer can be 0.1% by mass or more and 8% by mass or less, usually preferably 5% by mass or less, and more preferably 2% by mass or less. The technology disclosed herein can also be carried out in a form in which the negative electrode active material layer does not contain a filler.

[0087] The negative electrode active material layer may further contain other components besides the negative electrode active material, conductive agent, binder, thickener, and filler. These other components may include those unintentionally present in the negative electrode active material layer. Furthermore, the negative electrode active material layer may contain impurities that have been unintentionally included as these other components, insofar as they achieve the effects of the present invention. The upper limit of the content of these other components in the negative electrode active material layer may be 10% by mass, 5% by mass, 2% by mass, 1% by mass, 0.1% by mass, or 0.01% by mass. The upper limit of the content of unintentionally present components in the negative electrode active material layer may be 10% by mass, 5% by mass, 2% by mass, 1% by mass, 0.1% by mass, or 0.01% by mass. The upper limit of the content of unintentionally present impurities in the negative electrode active material layer may be 10% by mass, 5% by mass, 2% by mass, 1% by mass, 0.1% by mass, or 0.01% by mass.

[0088] The thickness of the negative electrode active material layer is set appropriately according to the type of negative electrode active material, the application of the non-aqueous electrolyte energy storage element, etc. The average thickness of one negative electrode active material layer may be, for example, 5 μm or more and 1,000 μm or less. The lower limit of the average thickness of one negative electrode active material layer may be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, or 100 μm. The upper limit of the average thickness of one negative electrode active material layer may be 800 μm, 500 μm, 200 μm, 100 μm, 80 μm, 60 μm, or 40 μm. The mass per unit area of ​​one negative electrode active material layer may be, for example, 2 mg / cm². 2 More than 50mg / cm 2 The following is also acceptable: The lower limit of the mass per unit area of ​​one negative electrode active material layer is 3 mg / cm². 2 , 4 mg / cm³ 2 , 5 mg / cm³ 2 or 6 mg / cm³ 2 It may also be the case that the upper limit of the mass per unit area of ​​one negative electrode active material layer is 30 mg / cm³. 2 , 20 mg / cm³ 2 , 15 mg / cm³ 2 , 12 mg / cm³ 2 or 10 mg / cm³ 2 That's fine.

[0089] The porosity of the negative electrode active material layer may be, for example, 30% to 70%. The lower limit of the porosity of the negative electrode active material layer may be 35%, 40%, or 45%. The upper limit of the porosity of the negative electrode active material layer may be 60%, 50%, or 40%.

[0090] For example, the upper limit of the BET specific surface area of ​​the negative electrode active material layer is 5 m². 2 / g or 4m 2 / g is also acceptable, but 3m 2 It is preferable that it be / g, and 2.9m 2 It is more preferable that the BET specific surface area of ​​the negative electrode active material layer is below the above upper limit, which can further improve the capacity retention rate of the non-aqueous electrolyte energy storage element after charge-discharge cycles. The lower limit of the BET specific surface area of ​​the negative electrode active material layer is 1 m 2 / g is preferred, 2m 2 / g is more preferable, 2.5m 2 / g is even more preferable. By having the BET specific surface area of ​​the negative electrode active material layer be greater than or equal to the above lower limit, it is possible to further reduce the resistance of the non-aqueous electrolyte energy storage element under low-temperature conditions.

[0091] (Method of manufacturing the negative electrode) The negative electrode can be manufactured by known methods. The negative electrode can be manufactured, for example, by applying a paste-like negative electrode mixture (negative electrode mixture paste) directly to the negative electrode substrate or via an intermediate layer, and drying it to form a negative electrode active material layer, similar to the manufacturing method of the positive electrode described above. After drying, the negative electrode active material layer may be pressed or otherwise subjected to other processes.

[0092] (Separator) A known separator can be used. Examples of separators include a separator consisting only of a substrate layer, or a separator in which an inorganic layer containing inorganic particles and a binder is formed on one or both sides of the substrate layer.

[0093] Examples of the substrate layer form of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these forms, porous resin film is preferred from the viewpoint of strength, and nonwoven fabric is preferred from the viewpoint of liquid retention of non-aqueous electrolytes. The material of the substrate layer of the separator is not particularly limited as long as it has insulating properties, but resins such as polyolefins (polyethylene, polypropylene, etc.), polyimide, and aramid are preferred.

[0094] Examples of inorganic compounds constituting inorganic particles include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, and magnesium oxide; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ionic crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon; mineral resource-derived materials such as talc, zeolite, kaolin, bentonite, and mica, or their artificial counterparts. One or more types of inorganic particles can be used. The average particle size of the inorganic particles is preferably, for example, 0.5 μm to 10 μm. The inorganic particle content in the inorganic layer is preferably 50% to 99% by mass, and more preferably 80% to 98% by mass.

[0095] Examples of binders used in the inorganic layer include those similar to those exemplified in the positive electrode active material layer.

[0096] The porosity of the separator may be, for example, 20% or more and 80% or less. The lower limit of the separator's porosity may be 30%, 40%, or 50% from the viewpoint of discharge performance, etc. The upper limit of the separator's porosity may be 70%, 60%, or 50% from the viewpoint of strength, etc. In this specification, "porosity" refers to a volume-based value and means a measurement value obtained with a mercury porosimeter.

[0097] The average thickness of the separator may be, for example, 10 μm to 40 μm, or 15 μm to 30 μm.

[0098] A polymer gel composed of a polymer and a non-aqueous electrolyte may be used as a separator. A polymer gel may also be used in combination with a porous resin film, nonwoven fabric, etc., as described above, as a separator.

[0099] (electrode body) As the electrode body, known structures such as wound electrode bodies and laminated electrode bodies can be used.

[0100] A wound electrode has a structure in which the positive electrode and negative electrode are wound together while being insulated. The wound electrode may be cylindrical or flattened. The electrode 2 of the non-aqueous electrolyte energy storage element 1 in Figure 1 is a flattened wound electrode. A wound electrode can be manufactured, for example, by the following procedure. First, a laminate is obtained by stacking strip-shaped positive electrode, separator, and negative electrode in that order. A wound electrode is obtained by winding this laminate.

[0101] A laminated electrode body has a structure in which one or more positive electrodes and one or more negative electrodes are stacked in an insulated state. For example, a laminated electrode body can be obtained by stacking rectangular positive electrodes, separators, and negative electrodes in this order.

[0102] Other electrode structures can also be used, such as those in which at least one of the positive and negative electrodes is folded in a bellows-like manner and stacked.

[0103] (Non-aqueous electrolytes) A known non-aqueous electrolyte can be used as the non-aqueous electrolyte. A non-aqueous electrolyte is a medium that carries charge transport ions (e.g., lithium ions) between the positive and negative electrodes and is substantially free of water. The water content in the non-aqueous electrolyte may be, for example, 10,000 ppm or less, 5,000 ppm or less, 1,000 ppm or less, 500 ppm or less, 100 ppm or less, preferably 50 ppm or less, and more preferably 20 ppm or less. Examples of non-aqueous electrolytes include non-aqueous electrolyte solutions and solid electrolytes. Non-aqueous electrolyte solutions and solid electrolytes may be used in combination. It is preferable to use a non-aqueous electrolyte solution, and more preferable to use only a non-aqueous electrolyte solution.

[0104] (Non-aqueous electrolyte) A non-aqueous electrolyte contains a non-aqueous solvent and an electrolyte salt dissolved in this non-aqueous solvent.

[0105] Any known non-aqueous solvent can be used. Examples of non-aqueous solvents include carbonates, esters, ethers, amides, and nitriles. Examples of carbonates include cyclic carbonates and linear carbonates. Examples of esters include carboxylic acid esters, phosphate esters, and sulfonic acid esters. As non-aqueous solvents, compounds in which some of the hydrogen atoms contained in these compounds are substituted with halogen atoms may also be used. One or more non-aqueous solvents can be used.

[0106] A cyclic carbonate refers to a carbonate having a ring structure containing a carbonate group (-OC(=O)-O-). Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, vinylethylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, styrene carbonate, 1-phenylvinylene carbonate, and 1,2-diphenylvinylene carbonate. A cyclic carbonate may be a saturated cyclic carbonate such as ethylene carbonate, or an unsaturated cyclic carbonate such as vinylene carbonate. "Saturated" means not having carbon-carbon unsaturated bonds (carbon-carbon double bonds and carbon-carbon triple bonds). "Unsaturated" means having carbon-carbon unsaturated bonds. As a cyclic carbonate, a saturated cyclic carbonate is preferred, and ethylene carbonate is more preferred.

[0107] A chain-like carbonate refers to a carbonate that does not have a ring structure containing a carbonate group. Examples of chain-like carbonates include diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, diphenyl carbonate, trifluoroethyl methyl carbonate, and bis(trifluoroethyl) carbonate. The chain-like carbonate may be a saturated chain-like carbonate such as dimethyl carbonate, or an unsaturated chain-like carbonate such as diphenyl carbonate. A saturated chain-like carbonate is preferred as the chain-like carbonate, and ethyl methyl carbonate is more preferred.

[0108] The non-aqueous solvent preferably contains carbonate, and more preferably contains both cyclic carbonate and linear carbonate. The carbonate content in the non-aqueous solvent is preferably 80% to 100% by volume, may be 99% to 100% by volume, or 100% by volume. Using cyclic carbonate can promote the dissociation of the electrolyte salt and increase the ionic conductivity of the non-aqueous electrolyte. Using linear carbonate can keep the viscosity of the non-aqueous electrolyte low. When using both cyclic carbonate and linear carbonate, the volume ratio of cyclic carbonate to linear carbonate (cyclic carbonate:linear carbonate) is preferably in the range of 5:95 to 50:50.

[0109] Any known electrolyte salt can be used. Examples of electrolyte salts include lithium salts, sodium salts, potassium salts, magnesium salts, and onium salts. Among these, lithium salts are preferred. One or more electrolyte salts can be used.

[0110] Examples of lithium salts include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, and LiClO4; imide salts such as LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9); and lithium oxalate salts such as LiB(C2O4)2, LiBF2(C2O4), and LiPF2(C2O4)2. LiN(SO2F)2 is also an inorganic lithium salt. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred. Imide salts are also sometimes preferred.

[0111] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm³ at 20°C and 1 atm. 3 More than 2.5mol / dm 3 The following is preferred: 0.3 mol / dm 3 More than 2.0mol / dm 3 The following is more preferable: 0.5 mol / dm 3 More than 1.7mol / dm 3The following is even more preferable: 0.7 mol / dm 3 More than 1.5mol / dm 3 The following is particularly preferable. By setting the electrolyte salt content within the above range, the ionic conductivity of the non-aqueous electrolyte can be increased.

[0112] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and electrolyte salt. One or more types of additives may be used. When additives are used in the non-aqueous electrolyte, the additive content in the non-aqueous electrolyte is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 7% by mass or less, even more preferably 0.2% by mass or more and 5% by mass or less, and particularly preferably 0.3% by mass or more and 3% by mass or less.

[0113] (solid electrolyte) The solid electrolyte can be selected from any material that has ionic conductivity, such as lithium, sodium, or calcium, and is solid at room temperature (e.g., 20°C). Examples of solid electrolytes include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, halide solid electrolytes, and polymer solid electrolytes. One or more types of solid electrolytes can be used.

[0114] (container) The container houses the electrode body and non-aqueous electrolyte within its internal space. The container material can be a metal material such as aluminum or stainless steel, or a resin material; metal materials are preferred from the viewpoint of strength, etc. Composite materials of metal and resin materials can also be used.

[0115] The shape of the container is not particularly limited, but it can be cylindrical, rectangular (square), disc-shaped, etc. The container may also be in the form of a sheet or other shape formed from a metal-resin composite film.

[0116] (Shape, application, etc. of non-aqueous electrolyte energy storage elements) The shape of the non-aqueous electrolyte energy storage element according to one embodiment of the present invention is not particularly limited. The non-aqueous electrolyte energy storage element may be, for example, a cylindrical battery, a prismatic battery, a flat battery, a coin cell battery, a button cell battery, etc.

[0117] The applications of the non-aqueous electrolyte energy storage element according to one embodiment of the present invention are not particularly limited. For example, the non-aqueous electrolyte energy storage element can be used as a power source for automobiles such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles, as well as for electronic devices such as personal computers and communication terminals, and as a power storage power source. The non-aqueous electrolyte energy storage element according to one embodiment of the present invention has the advantages of low resistance under low-temperature conditions and high capacity retention after charge-discharge cycles. Taking full advantage of these advantages, it can be suitably used as a power source for automobiles, and in particular suitably used as a power source for hybrid vehicles.

[0118] The non-aqueous electrolyte energy storage element of the present invention can be used individually or in combination. The non-aqueous electrolyte energy storage element may be used individually when the required output and voltage are small. On the other hand, when at least one of the required output and voltage is large, the non-aqueous electrolyte energy storage element may be used as part of an energy storage device combined with other non-aqueous electrolyte energy storage elements. In an energy storage device composed of multiple non-aqueous electrolyte energy storage elements, at least one of the non-aqueous electrolyte energy storage elements included in the energy storage device may be a non-aqueous electrolyte energy storage element according to one embodiment of the present invention. The energy storage device will be described in detail later.

[0119] In the non-aqueous electrolyte energy storage element according to one embodiment of the present invention, the container may be restrained to maintain a certain thickness, or it may not be restrained in such a way. Alternatively, the container may be restrained to have a certain load applied to it. When the container is restrained, expansion of the container due to charge-discharge cycles, etc., may be suppressed, and a decrease in charge-discharge performance may be suppressed. When the container is restrained, the electrode body inside the container may or may not have a load applied to it. For example, the non-aqueous electrolyte energy storage element or energy storage device may be provided with a restraining member that performs such restraint.

[0120] <Method for manufacturing a non-aqueous electrolyte energy storage element> A non-aqueous electrolyte energy storage element according to one embodiment of the present invention can be manufactured by known methods. The manufacturing method of the non-aqueous electrolyte energy storage element includes, for example, preparing a positive electrode, preparing a negative electrode, preparing a non-aqueous electrolyte, and housing the positive electrode, negative electrode, and non-aqueous electrolyte in a container. The manufacturing method may also include preparing a separator, and manufacturing an electrode body using the positive electrode, negative electrode, and separator. Housing the positive electrode, negative electrode, and non-aqueous electrolyte in a container may be equivalent to housing the electrode body and non-aqueous electrolyte in a container.

[0121] Preparing the positive electrode may also mean manufacturing the positive electrode. The positive electrode can be manufactured by the method described above. Preparing the negative electrode may also mean manufacturing the negative electrode. The negative electrode can be manufactured by the method described above. Preparing the non-aqueous electrolyte may also mean preparing the non-aqueous electrolyte. The non-aqueous electrolyte can be prepared, for example, by dissolving an electrolyte salt in a non-aqueous solvent. The positive electrode, negative electrode, separator, non-aqueous electrolyte, etc., may be prepared by purchase or other means.

[0122] The electrode body (or positive and negative electrode) and the non-aqueous electrolyte can be housed in a container by known methods. If the non-aqueous electrolyte is a non-aqueous electrolyte solution, for example, the electrode body (or positive and negative electrode) can be housed in the container first, and then the non-aqueous electrolyte solution can be injected through an inlet provided in the container. The inlet is sealed after the non-aqueous electrolyte solution is injected. The method for manufacturing the non-aqueous electrolyte energy storage element may further include initial charging and discharging of the assembled uncharged / discharged energy storage element.

[0123] The non-aqueous electrolyte energy storage element according to one embodiment of the present invention may be manufactured by other methods. For example, if the non-aqueous electrolyte energy storage element according to one embodiment of the present invention is an all-solid-state battery, it may be manufactured by pressing the forming materials of the positive electrode, separator, and negative electrode individually or collectively.

[0124] <Energy storage device> The energy storage device 30 in Figure 2 comprises a plurality of energy storage units 20. Each energy storage unit 20 comprises a plurality of electrically connected non-aqueous electrolyte energy storage elements 1. The energy storage device 30 may also include busbars (not shown) for electrically connecting the plurality of non-aqueous electrolyte energy storage elements 1, busbars (not shown) for electrically connecting the plurality of energy storage units 20, etc. The energy storage unit 20 or the energy storage device 30 may also include a condition monitoring device (not shown) for monitoring the state of one or more non-aqueous electrolyte energy storage elements 1.

[0125] <Other Embodiments> The non-aqueous electrolyte energy storage element of the present invention is not limited to the embodiments described above, and various modifications may be made without departing from the spirit of the invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or with well-known technology. Furthermore, a part of the configuration of one embodiment may be deleted. Also, well-known technology may be added to the configuration of one embodiment.

[0126] In the above embodiment, a case in which a non-aqueous electrolyte energy storage element is used as a rechargeable non-aqueous electrolyte secondary battery was described, but the type, shape, dimensions, capacity, etc. of the non-aqueous electrolyte energy storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double-layer capacitors, lithium-ion capacitors, and other capacitors.

[0127] In the above embodiment, an electrode body in which a separator is interposed between the positive electrode and the negative electrode was described, but the electrode body does not need to have a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other, with a non-conductive layer formed on the active material layer of either the positive electrode or the negative electrode. Thus, the positive electrode and the negative electrode may further have layers other than the base material, intermediate layer, and active material layer. Furthermore, the positive electrode and the negative electrode do not need to have a layered structure. [Examples]

[0128] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0129] [Example 1] (Fabrication of the positive electrode) LiNi is a secondary particle of lithium transition metal composite oxide with an internal porosity of 19% and an average particle size of 4 μm. 0.45 Co 0.35 Mn 0.20 I prepared O2. A positive electrode mixture paste was prepared using the above-mentioned lithium transition metal composite oxide particles, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of lithium transition metal composite oxide particles, AB, and PVDF was 91.5:6.0:2.5 (on a solid content basis). The positive electrode mixture paste was applied to both sides of an aluminum foil used as the positive electrode substrate and dried. Subsequently, a roll press was performed to obtain a positive electrode with a positive electrode active material layer formed on it.

[0130] (Fabrication of the negative electrode) Natural graphite particles were prepared by mixing first-generation natural graphite particles with an internal porosity of 0.5% and a D50 particle size of 7.9 μm with second-generation natural graphite particles with an internal porosity of 0.5% and a D50 particle size of 13.8 μm in a 50:50 mass ratio. The D50 particle size of the natural graphite particles was 11.6 μm, and the ratio of D10 particle size to D90 particle size (D10 / D90) was 0.25. The BET specific surface area of ​​the natural graphite particles was 2.7 m². 2 / g or more 2.8m 2 It was less than / g. A negative electrode mixture paste was prepared using the above-mentioned natural graphite particles, styrene-butadiene rubber (SBR) as a binder, carboxymethylcellulose (CMC) as a thickener, and water as a dispersion medium. The mass ratio of natural graphite particles, SBR, and CMC was 98.6:0.8:0.6 (on a solid content basis). The negative electrode mixture paste was applied to both sides of a copper foil used as the negative electrode substrate and dried. Subsequently, a roll press was performed to obtain a negative electrode with a negative electrode active material layer formed thereon. The BET specific surface area of ​​the negative electrode active material layer was 2.6 m². 2 It was / g.

[0131] (Non-aqueous electrolytes) A solvent prepared by mixing ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 30:35:35, containing 1.2 mol / dm³ 3 LiPF6 was dissolved at the specified concentration to obtain a non-aqueous electrolyte.

[0132] (Separator) A microporous membrane made of polyolefin was used as the separator.

[0133] (Assembly of non-aqueous electrolyte energy storage elements) A flat, wound electrode body was obtained using the above positive electrode, the above negative electrode, and the above separator. The obtained electrode body was placed in a rectangular container, the above non-aqueous electrolyte was injected and the container was sealed to obtain the non-aqueous electrolyte energy storage element of Example 1.

[0134] [Examples 2 to 4 and Comparative Examples 1 to 18] As shown in Table 1, non-aqueous electrolyte energy storage elements for Example 3 and Comparative Examples 2 to 4, 7, 9 to 11, 13 to 16, and 18 were obtained in the same manner as in Example 1, except that the ratio of Ni, Co, and Mn in the lithium transition metal composite oxide particles was changed, the amount of conductive agent in the positive electrode active material layer was changed, and natural graphite particles with a changed mixing ratio of first natural graphite particles and second natural graphite particles were used. As shown in Table 1, non-aqueous electrolyte energy storage elements for Comparative Examples 1, 6, 8, and 17 were obtained in the same manner as in Example 1, except that the ratio of Ni, Co, and Mn in the lithium transition metal composite oxide particles was changed, the amount of conductive agent in the positive electrode active material layer was changed, and natural graphite particles with an internal porosity of 0.5% and a D50 particle size of 7.4 μm were used alone. As shown in Table 1, non-aqueous electrolyte energy storage elements were obtained in Examples 2 and 4 and Comparative Examples 5 and 12, in the same manner as in Example 1, except that the ratio of Ni, Co, and Mn in the lithium transition metal composite oxide particles was changed, the amount of conductive agent in the positive electrode active material layer was changed, and natural graphite particles with an internal porosity of 0.5% and a D50 particle size of 13.7 μm were used alone. Table 1 shows the D50 particle size and D10 / D90 of each natural graphite particle, as well as the BET specific surface area of ​​the negative electrode active material layer. Note that the BET specific surface area of ​​the natural graphite particles was 2.7 m² in all cases. 2 / g or more 2.8m 2 It was above / g.

[0135] [evaluation] (1)Initial charge / discharge Each obtained non-aqueous electrolyte energy storage element underwent initial charging and discharging under the following conditions: Constant current charging was performed in a 25°C constant temperature bath with a charging current of 1.0C and a charging termination voltage of 4.1V, followed by constant voltage charging at 4.1V. Charging was terminated when the total charging time reached 3 hours. A 10-minute rest period was then observed. Constant current discharge was performed with a discharge current of 1.0C and a discharge termination voltage of 3.0V. The discharge capacity obtained during the above discharge was defined as the initial discharge capacity.

[0136] (2) Measurement of resistance under low temperature conditions For each non-aqueous electrolyte energy storage element, constant current charging was performed at 25°C with a current of 1.0C to 30% of the initial discharge capacity (discharge capacity in the initial charge / discharge described above), bringing the State of Charge (SOC) to 30%. After being stored in a -10°C constant temperature bath for 4 hours, the elements were discharged for 10 seconds each at currents of 1C, 1.3C, or 1.5C. After each discharge, constant current charging was performed at a current of 0.2C to bring the SOC to 30%. The relationship between the current in each discharge and the voltage at 10 seconds after the start of discharge was plotted, and the DC resistance under low temperature conditions (low-temperature DCR) was determined from the slope of the approximate straight line of the three plots. The results are shown in Table 1 as relative values ​​with the low-temperature DCR of Comparative Example 1 set to 100.0%.

[0137] (3) Charge-discharge cycle test Next, each non-aqueous electrolyte energy storage element was subjected to constant current discharge at 25°C with a current of 1.0C and a discharge termination voltage of 3.0V to bring the State of Charge (SOC) to 0%, and then charged with a constant current of 0.5C to an amount of charge equivalent to 50% of the SOC. Subsequently, it was stored in a constant temperature bath at 60°C for 4 hours. Then, it was charged with a constant current of 10C to a voltage equivalent to 80% of the SOC, and then discharged with a constant current of 10C to a voltage equivalent to 20% of the SOC. The above charging and discharging cycles were repeated for 1,000 hours without any rest periods between charging and discharging cycles.

[0138] (4) Measurement of capacity retention rate after charge-discharge cycle After performing the above charge-discharge cycle test, each non-aqueous electrolyte energy storage element was subjected to constant current discharge at 25°C with a current of 1.0C and a discharge termination voltage of 3.0V to bring the State of Charge (SOC) to 0%. Then, under the same conditions as the initial charge-discharge test described above, the discharge capacity after the charge-discharge cycle test was measured. The percentage of the discharge capacity after the charge-discharge cycle test relative to the initial discharge capacity was calculated as the capacity retention rate after the charge-discharge cycle. The results are shown in Table 1.

[0139] [Table 1]

[0140] As shown in Examples 1 to 4, when lithium transition metal composite oxide particles with a nickel content of 40 mol% or more and a cobalt content of 30 mol% or more were used in the positive electrode, the internal porosity of the lithium transition metal composite oxide particles was 15% or more, the conductive agent content in the positive electrode active material layer was 5% by mass or more and 10% by mass or less, and graphite particles with a D50 particle size of 11 μm or more and a ratio of D10 particle size to D90 particle size (D10 / D90) of 0.2 or more and 0.35 or less were used in the negative electrode, it was possible to achieve both a low-temperature DCR (relative value) of less than 91% and a capacity retention rate of 82.2% or more after charge-discharge cycles. In contrast, in Comparative Examples 1 to 18, which did not satisfy any of the above configurations, the low-temperature DCR (relative value) was 91% or more, or the capacity retention rate after charge-discharge cycles was less than 82.2%. [Industrial applicability]

[0141] This invention can be applied to non-aqueous electrolyte energy storage elements used as power sources for electronic devices such as personal computers and communication terminals, as well as for automobiles and industrial applications. [Explanation of Symbols]

[0142] 1. Non-aqueous electrolyte energy storage element 2 Electrode body 3 containers 4 Positive lead 5. Positive external terminal 6 Negative lead 7. Negative external terminal 20 Energy storage units 30 Energy storage devices

Claims

1. A positive electrode having a positive electrode active material layer containing lithium transition metal composite oxide particles and a conductive agent, A negative electrode having a negative electrode active material layer containing graphite particles Equipped with, The above lithium transition metal composite oxide particles contain nickel, cobalt, and manganese elements. In the above lithium transition metal composite oxide particles, the content of the nickel element among all metal elements other than lithium is 40 mol% or more, and the content of the cobalt element is 30 mol% or more. The internal porosity of the above lithium transition metal composite oxide particles is 15% or more. The content of the conductive agent in the positive electrode active material layer is 5% by mass or more and 10% by mass or less. The D50 particle size of the above graphite particles is 11 μm or more and 16 μm or less. A non-aqueous electrolyte energy storage element in which the ratio of D10 particle size to D90 particle size (D10 / D90) in the above graphite particles is 0.2 or more and 0.35 or less.

2. The non-aqueous electrolyte energy storage element according to claim 1, wherein the internal porosity of the graphite particles is 2% or less.

3. The BET specific surface area of ​​the above graphite particles is 3 m². 2 A non-aqueous electrolyte energy storage element according to claim 1 or claim 2, wherein the amount is less than or equal to / g.

4. The non-aqueous electrolyte energy storage element according to claim 1 or claim 2, wherein the molar ratio of the content of the cobalt element to the content of the manganese element in the lithium transition metal composite oxide particles is 1.2 or more.

Citation Information

Patent Citations

  • Nonaqueous electrolyte power storage element

    WO2023090333A1